2022
DOI: 10.2147/jpr.s376681
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study Between Early versus Late Intraperitoneal Administration of Either Bupivacaine/Tramadol or Bupivacaine/Dexmedetomidine for Perioperative Analgesia in Abdominal Laparoscopic Cancer Surgeries: A Prospective Randomized Study

Abstract: Objective Several modalities for analgesia after laparoscopic procedures have been used. This study aimed to investigate the efficacy of early versus late bupivacaine/tramadol combination and bupivacaine/dexmedetomidine combination in analgesia for laparoscopic cancer surgeries. Methods A total of 100 patients of both genders scheduled for elective laparoscopic cancer surgeries were included. Patients were randomly assigned to one of four groups each comprises 25 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They also found that this method significantly reduced the need for postoperative analgesic and antiemetic medications. 24…”
Section: Figure-1mentioning
confidence: 99%
“…They also found that this method significantly reduced the need for postoperative analgesic and antiemetic medications. 24…”
Section: Figure-1mentioning
confidence: 99%